Clinical Features and Functional Outcome of Patients with Non-compressive Myelopathy: A Hospital Based Cross Sectional Study from a Tertiary Care Center of Dhaka - Roy, Liton Kumar; Hasan, Md Hasibul; Sarker, Humayun Kabir; Dhar, Kingshuk; Habib, Mansur; Kamal, Mohammad Mostafa (Journal of Dhaka Medical College, 2025)
Background: Non-compressive myelopathy (NCM) has a wide temporal and clinical profile with etiology that varies over different geographical locations. The etiology may vary according to age, sex, geographical location and other associated factors. There remains a great deal of heterogeneity in clinical features and imaging findings. The functional outcome also differ according to etiology, extent of involvement and rapidity of the management. Aims: To evaluate the clinical features and functional outcome of patients with non-compressive myelopathy. Methods: This observational study was carried out in the Department of Neurology, Neurosurgery and Medicine of Dhaka Medical College Hospital, Dhaka, during January2018 to December 2019. A total of 84 patients suffering from non-compressive myelopathy were included in this study. Age >18 years, both male and female patients with features of myelopathy admitted within 14 days of onset were enrolled in this study and followed up for 180 days. Results: 40 (47.5%) patients had acute transeverse myelitis (ATM) without spinal shock followed by 26(30.9%) had ATM with spinal shock, 9(10.8%) had multiple sclerosis (MS), 6(7.2%) had neuromyelitis optica (NMO) and 3(3.6%) had neuromyelitis optica specterum disorders (NMOSD). More than one third (38.2%) patients belonged to age 18-20 years followed by 22(26.3%) in 21- 30 years, 20 (23.9%) in 31-40 years, 6(7.2%) in 41-50 years and 4(4.8%) in >50 years. Male to female ratio was almost 2:1. Almost two third (63.1%) patients had paraplegia and 31(36.9%) had quadriplegia. Three fourth (75.0%) patients had sudden onset and 21(25.0%) had insidious onset. More than three fourth (84.5%) patients had sensory involvement. Two third (65.5%) patients had bowel and bladder involvement. The mean Modified Rankin Scale (MRS) score on admission was 4.3±0.86 and 3.13±1.15 at 180 days. The difference was statistically significant (p<0.05) between MRS score on admission and MRS score at 180 days. Almost half (48.0%) patients had improved MRS score, followed by 20(20.0%) static, 16(16.0%) worse. The mean barthel index was 34.35±16.71 and 50.06±19.75 on admission and at 180 days (p value <0.01). More than half (53.0%) patients had improved barthel index, followed by 22(22.0%) worse, 16(16.0%) lost to follow up and 9(9.0%) static. Conclusion: ATM was the most common diagnosis among non-compressive myelopathy; with the 2nd decade of the life being the most common age group and predominantly affecting male. Patients with non compressive myelopathy most commonly presented with paraplegia, sudden onset symptoms, sensory involvement, bowel and bladder dysfunction. More than half of the patient improved at day 180. J Dhaka Med Coll. 2023; 32(2) : 131-138